2018
DOI: 10.1002/jsfa.8844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwave‐assisted hot water treatments designed against Mexican fruit fly (Anastrepha ludens) on grapefruit (Citrus paradisi) quality

Abstract: MW-HWT was shorter (130 min) and had a lesser effect on the quality of the grapefruit when compared with fruits under HWT (188 min duration). Thus, this treatment could be considered as an alternative method against the Mexican fruit fly in grapefruit. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Biomass Type. Since Krzan et al first applied microwave energy to liquefaction [19,20], a variety of biomass types including sweetgum sawdust [8]; agricultural residues including bagasse, corn stover, rice straw, wheat straw, cotton stalk, and corncobs [24][25][26]; organosolv lignin of olive tree prunings [27]; Sargassum polycystum C. Agardh [28]; microalgae [29]; Ulva prolifera [30]; wheat straw alkali lignin International Journal of Polymer Science [31]; sugar beet pulp [32]; peony oil palm empty fruit bunch fiber [16]; oil palm empty fruit bunch cellulose [33]; poplar; Chinese fir; bamboo; hemp xyloid stem [22]; mixed softwood pellets [34]; banana pseudostem [35]; coconut fiber [36]; and grapefruit [37] have been studied as raw materials for microwave-assisted liquefaction for the production of renewable chemical platforms and/or biobased materials. The chemical composition (cellulose, hemicellulose, lignin, and ash) and microstructure of the lignocellulose feedstocks greatly differed with each other, which may influence their liquefaction behaviors under microwave heating.…”
Section: Lignocellulosic Biomass Sources Formentioning
confidence: 99%
“…Biomass Type. Since Krzan et al first applied microwave energy to liquefaction [19,20], a variety of biomass types including sweetgum sawdust [8]; agricultural residues including bagasse, corn stover, rice straw, wheat straw, cotton stalk, and corncobs [24][25][26]; organosolv lignin of olive tree prunings [27]; Sargassum polycystum C. Agardh [28]; microalgae [29]; Ulva prolifera [30]; wheat straw alkali lignin International Journal of Polymer Science [31]; sugar beet pulp [32]; peony oil palm empty fruit bunch fiber [16]; oil palm empty fruit bunch cellulose [33]; poplar; Chinese fir; bamboo; hemp xyloid stem [22]; mixed softwood pellets [34]; banana pseudostem [35]; coconut fiber [36]; and grapefruit [37] have been studied as raw materials for microwave-assisted liquefaction for the production of renewable chemical platforms and/or biobased materials. The chemical composition (cellulose, hemicellulose, lignin, and ash) and microstructure of the lignocellulose feedstocks greatly differed with each other, which may influence their liquefaction behaviors under microwave heating.…”
Section: Lignocellulosic Biomass Sources Formentioning
confidence: 99%
“…It might be a valuable research to used water as microwave heating mediums to reduce AFB 1 in corn. In the literature, there were some researchers reported that the combination of water and microwaves had high potential as a postharvest disinfestation treatment [ 19 ]. However, the information on the combined effects of water and microwaves on AFB 1 reduction of corn was lacking.…”
Section: Introductionmentioning
confidence: 99%